1998
DOI: 10.1902/jop.1998.69.9.962
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Findings in Elderly Patients With Non‐Insulin Dependent Diabetes Mellitus

Abstract: The periodontal status of 25 patients with non-insulin dependent diabetes mellitus (NIDDM) (age range 58 to 76) was investigated and compared with 40 non-diabetic control subjects (age range 59 to 77). Surfaces with visible plaque and bleeding after probing, calculus, recessions, and pathological pockets were examined. The total attachment loss was calculated as a sum of recessions and pockets in millimeters. Mesial and distal bone loss was measured from panoramic radiographs and mean alveolar bone loss was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 33 publications
10
137
1
4
Order By: Relevance
“…Comparisons between the studies are difficult due to the varying clinical and laboratory protocols that were utilized. Also, there are a number of other studies of the periodontal microbiota in diabetes not included in Table 1, which are inconclusive as they did not adequately report or control for the clinical periodontal status of the patients involved in the research (Sanchez-Cordero et al 1979, Thorstensson et al 1995, Novaes et al 1997, Collin et al 1998, Campus et al 2005, Ciantar et al 2005, Hintao et al 2007, Colhoun et al 2008, Dasanayake et al 2008, Kamaraj et al 2011 or because they did not present statistical analysis in support of stated conclusions (Zambon et al 1988). Therefore, in these studies, it is not always clear if identified differences in the periodontal microbiota between diabetic and non-diabetic patients result truly from an impact of the diabetic state on the periodontal bacteria, or simply result from more severe periodontitis (i.e.…”
Section: Microbial Factorsmentioning
confidence: 99%
“…Comparisons between the studies are difficult due to the varying clinical and laboratory protocols that were utilized. Also, there are a number of other studies of the periodontal microbiota in diabetes not included in Table 1, which are inconclusive as they did not adequately report or control for the clinical periodontal status of the patients involved in the research (Sanchez-Cordero et al 1979, Thorstensson et al 1995, Novaes et al 1997, Collin et al 1998, Campus et al 2005, Ciantar et al 2005, Hintao et al 2007, Colhoun et al 2008, Dasanayake et al 2008, Kamaraj et al 2011 or because they did not present statistical analysis in support of stated conclusions (Zambon et al 1988). Therefore, in these studies, it is not always clear if identified differences in the periodontal microbiota between diabetic and non-diabetic patients result truly from an impact of the diabetic state on the periodontal bacteria, or simply result from more severe periodontitis (i.e.…”
Section: Microbial Factorsmentioning
confidence: 99%
“…We found only 1 reference stating this possibility in the medical literature, 28 whereas extensive evidence has been compiled in dental literature. 4,29,30 Hyperglycemia induces nonenzymatic glycation of proteins, and resultant AGEs are known to stimulate macrophages to express cytokines (e.g., IL-6 and TNF-α). These cytokines induce the liver to secrete acute phase reactants that are implicated in the inflammatory process related to atherogenesis.…”
Section: Diabetes Endothelial Dysfunction and Atherosclerosismentioning
confidence: 99%
“…It is one of the main contributing factors for periodontal disease and also limiting factor for periodontal treatments such as implant therapy. Although diabetes itself does not cause periodontitis, periodontal disease progresses more rapidly and leads to more tooth losses in patients with poorly controlled blood glucose [14][15][16][17][18] . Severe periodontitis has been associated with an increased risk of poor glycemic control and, in turn untreated advanced periodontal disease can deteriorate the metabolic control of diabetes 19) .…”
Section: +mentioning
confidence: 99%